The impact of family on gender: Women entrepreneurs in the construction industry - Raihanah Othman, Mastura Jaafar, Alireza Jalali, (Opción, 2019)
The first objective of this study is to explore the gender of women construction entrepreneurs (WCEs), while the second objective is to identify the influence of family on WCE via statistical analyses, including descriptive analysis, cross tabulation, and median split method. As a result, a majority of these WCEs with the gender of masculinity were raised in a large family, grew up under stringent discipline, and were exposed to open-minded parenting style. In conclusion, most WCEs seem to be raised in a large family under the authoritarian parenting style, with more than two siblings with the age spacing of 1-4 years.